Bridging Responsibility and Sustainability a Comprehensive Literature Review of CSR and its Role in Sustainable Development - Setya Atikatun Nabilah (Clean and Sustainability Business, 2025)
Objectives: This research aims to explore the strategic role of Corporate Social Responsibility (CSR) in advancing the Sustainable Development Goals (SDGs) by providing a comprehensive analysis of how CSR initiatives contribute to sustainable development practices. Research Design & Methods: This study used a systematic literature review to analyze 15 peer-reviewed scholarly articles published between 2019 and 2024. Articles were selected based on their relevance to CSR practices aligned with the SDGs and implications for corporate strategy and stakeholder engagement. Findings: The findings reveal that integrating CSR with the SDGs framework enables companies to design focused, balanced, and impactful strategies that address pressing social and environmental issues. This alignment enables more structured long-term planning and fosters positive stakeholder perceptions while contributing to the global sustainability agenda. In Indonesia, CSR implementation covers a wide range of sectors beyond heavy industry and is mandated by law, which highlights the importance of CSR in a variety of economic contexts. Implications & Recommendations: Companies are encouraged to adopt a strategic approach to CSR by embedding SDG principles into their core operations. This not only improves social and environmental outcomes but also enhances corporate performance, stakeholder trust, and risk management. Policymakers should further incentivize the adoption of CSR that is aligned with national development goals. Contribution & Value Added: This study confirms that aligning CSR with the SDGs has transformative potential in creating long-term value for business, society, and the environment. It also provides strategic guidance for corporate leaders, policymakers, and researchers on driving sustainable development.